Copper deficiency, a new triad: anemia, leucopenia, and myeloneuropathy - Shoaib M. Wazir; Ibrahim Ghobrial (Greater Baltimore Medical Center, 2017)
Clinical copper deficiency is now more frequently recognized. Hematologically, it can present as anemia (microcytic, normocytic, or macrocytic) and neutropenia. Thrombocytopenia is relatively rare. Neurologically, it can manifest as myelopathy and peripheral neuropathy simulating subacute combined degeneration. Bone marrow findings can mimic myelodysplasia resulting in occasional inappropriate referral for bone marrow transplantation. Other conditions with similar presentations include infections, drug toxicity, autoimmunity, B12 deficiency, folate deficiency, myelodysplastic syndrome, aplastic anemia, and lymphoma with bone marrow involvement. Hematological, but not neurological, manifestations respond promptly to copper replacement, making early diagnosis essential for good outcome. Common risk factors for copper deficiency are foregut surgery, dietary deficiency, enteropathies with malabsorption, and prolonged intravenous nutrition (total parenteral nutrition). We present a unique case of copper deficiency, with no apparent known risk factors.